Sabías Que… - Alvarado Vázquez, Marco A.; Salcedo Martínez, Sergio M.; Vargas López, Victor Ramón (Universidad Autónoma de Nuevo León, 2024)
Se presentan algunos datos interesantes sobre los usos de ciertas plantas, así como sobre su toxicidad.